Neutron reflection and small-angle neutron scattering studies of a fluorocarbon telomer surfactant. - Dupont, A; Eastoe, J; Barthélémy, P; Pucci, B; Heenan, R; Penfold, J; Steytler, D; Grillo, I (2003)
Dilute aqueous phase behavior of a novel tris(hydroxymethyl)acrylamidomethane (THAM)-derived telomer bearing a perfluorohexyl hydrophobic chain, F6THAM6, has been investigated. Fluorinated polyhydroxy surfactants of this kind find use in emerging biomedical applications. Neutron reflection (NR) and drop volume surface tension (DVT) methods have been used to determine the critical micelle concentration (cmc=4.7 x 10(-4) mol x dm(-3)) and surface adsorption parameters (at the cmc NR gives a molecular area a(cmc)=67.4 and 62 A(2) and surface excess gamma(cmc)=2.46 x 10(-6) mol x m(-2)). The aggregation structures were determined by small-angle neutron scattering (SANS), indicating globular (polydisperse spheres) micelles of radius approximately 30 A are present. These findings are compared with literature on surfactants with related structures, to identify how the unusual molecular structure of F6THAM6 affects surfactant properties.